ROS production is increased in the kidney but not in the brain of Dahl rats with salt hypertension elicited in adulthood - Vokurková, Martina; Rauchová, Hana; Řezáčová, Lenka; Vaněčková, Ivana; Zicha, Josef (Physiological research, 2015)
Enhanced production of superoxide radicals by nicotinamide-adenine dinucleotide phosphate (NADPH) oxidase in the brain and/or kidney of salt hypertensive Dahl rats has been proposed to participate in the pathogenesis of this form of experimental hypertension. Most information was obtained in young Dahl salt-sensitive (DS) rats subjected to high salt intake prior to sexual maturation. Therefore, the aim of our study was to investigate whether salt hypertension induced in adult DS rats is also accompanied with a more pronounced oxidative stress in the brain or kidney as compared to Dahl salt-resistant (DR) controls. NADPH oxidase activity as well as the content of thiobarbituric acid-reactive substances (TBARS) and conjugated dienes (oxidative index), which indicate a degree of lipid peroxidation, were evaluated in two brain regions (containing either hypothalamic paraventricular nucleus or rostral ventrolateral medulla) as well as in renal medulla and cortex. High salt intake induced hypertension in DS rats but did not modify blood pressure in DR rats. DS and DR rats did not differ in NADPH oxidase-dependent production of ROS, TBARS content or oxidative index in either part of the brain. In addition, high-salt diet did not change significantly any of these brain parameters. In contrast, the enhanced NADPH oxidase-mediated ROS production (without significant signs of increased lipid peroxidation) was detected in the renal medulla of salt hypertensive DS rats. Our findings suggest that there are no signs of enhanced oxidative stress in the brain of adult Dahl rats with salt hypertension induced in adulthood.
Keywords: Reactive Oxygen Species; kuchyňská sůl; Male; Rats; Blood Pressure; Brain; potkani inbrední Dahl; orgánová specificita; ledviny; Hypertension; Animals; Sodium Chloride, Dietary; zvířata; hypertenze; mužské pohlaví; mozek; reaktivní formy kyslíku; tkáňová distribuce; krevní tlak; krysa rodu Rattus; Oxidative Stress; oxidační stres; Rats, Inbred Dahl; Kidney; Tissue Distribution; Organ Specificity